The Burden of Anemia in Pregnancy Among Women Attending the Antenatal Clinics in Mkuranga District, Tanzania - Evelyine B. Ngimbudzi; Siriel N. Massawe; Bruno F. Sunguya (Frontiers Media S.A., 2021)
Introduction: The burden of anemia in pregnancy is of global health importance. Tanzania is no exception. Its effects vary from one region to another due to the differing causes. Overall, it is a significant cause of maternal mortality. This study sought to assess the prevalence and factors associated with anemia among pregnant women attending the antenatal clinic (ANC) in the Mkuranga district of the Pwani region of Tanzania.Methodology: This cross sectional study was conducted among 418 pregnant women aged 15-49 years attending the Mkuranga District Hospital and Kilimahewa Health Center. The outcome variable of interest was anemia in pregnancy defined as a hemoglobin concentration of 11 g/dl or less. Data was collected using face-to-face interviews with a standardized pretested questionnaire, and through blood samples collected for hemoglobin testing. Descriptive analysis was used to determine the prevalence of anemia while multiple logistic regression was used to determine factors associated with anemia in pregnancy.Results: Anemia was prevalent among 83.5% of pregnant women attending the two major ANCs in Mkuranga district. Categorically, the hemoglobin of 16.3% of the included women was normal, 51.9% had moderate anemia, 24.4% had mild anemia, and 7.2% had severe anemia. Factors associated with anemia included being in the third trimester (AOR = 2.87, p = 0.026), not consuming vegetables (AOR = 2.62, p = 0.008), meat (AOR = 2.71, p = 0.003), eggs (AOR = 2.98, p = 0.002), and fish (AOR = 2.38, p = 0.005). The finding of unadjusted analysis revealed that women with inadequate minimum dietary diversity were having significantly greater odds of being anemic as compared with those with adequate dietary diversity (OR = 1.94, P = 0.016).Conclusion: More than 80% of pregnant women attending ANC in Mkuranga districts were anemic. Such unprecedented burden of anemia is associated with several factors, which include poor dietary practices such as not consuming iron-rich foods, for example vegetables, meat, eggs, and fish. Women in their third trimester were also more likely to suffer from anemia. This unprecedented burden of anemia in pregnancy can be addressed if efforts to improve feeding practices and early monitoring at the ANCs are sustained.